Parkinson's disease delays predictable visual cue processing without affecting complex and unpredictable visual cue processing in postural control - Cruz, Caio Ferraz; Forti Barela, Ana Maria; Dona, Flavia; Genoves, Giovanna Gracioli; Ferraz, Henrique Ballalai; Cesar de Azevedo Silva, Sonia Maria; Barela, Jose Angelo [UNESP] (Elsevier B.V., 2021)
This study examined the influence of visual information of different complexities and predictability on the body sway of individuals with Parkinson's disease (PD) during upright stance. Twenty-one individuals at initial stages of PD (62.1 +/- 7.2 years), under dopaminergic medication, and 21 controls (62.3 +/- 7.1 years) stood inside a moving room, performing 10 trials of 60 s. In the first trial, the room remained motionless. Then, the room oscillated in an anterior-posterior direction. There were three blocks of three trials. In the first block, the room oscillated at 0.2 Hz (periodic simple condition); in the second block, periodic frequencies of 0.1, 0.3, and 0.5 Hz were combined (periodic complex condition); in the third block, non-periodic frequencies of 0.1, 0.3, and 0.5 Hz were combined (non-periodic complex condition). Participants were not informed about the room movement. The displacement of the room and trunk were registered using an OPTOTRAK system. Postural sway was examined using mean sway amplitude, and the relationship between visual information and body sway used coherence, gain, and phase. There was no group difference when the room remained motionless. Upon visual manipulation, the PD group displayed larger sway magnitude in the non-periodic complex condition. Individuals with PD also lagged behind the moving room (lower phase values) compared to controls, only in the periodic simple condition. In the remaining measures, there was no group difference. These results suggest that individuals with PD use complex and unpredictable visual information, similar to controls, during upright stance. However, PD might affect the predictable visual cues processing.
Keywords: Visual-motor coupling; Complexity; Predictability; Posture; Vision